Grade V small bowel injury after blunt abdominal trauma: a case report - Arjona Bojórquez, Rashid I.; Puerto Serrano, Isidro R.; Cervantes Sanchez, Aron; Ceseña Barrientos, Jonathan E.; Juan Hernandez, Orson R.; Navarrete Espinosa, Deysi L.; Salazar Quijano, Christian A.; Garcia Catalan, Grisell G.; Polanco Llanes, Alondrea S. (International Journal of Research in Medical Sciences, 2022)
Injury of the small intestine or mesentery that requires surgical intervention is relatively uncommon, presenting less than 1% of all trauma. Unstable hemodynamically patients with peritoneal irritation signs and stable hemodynamically patients with radiological signs of intestine or mesentery lesions need an exploratory laparotomy. A 33-year-old male patient, suffered a car accident in which he had a frontal impact collision and was between two structures for 30 minutes, and rescued by the fire department. Physical examination of the abdomen presents generalized pain on palpation of moderate intensity and rebound sign. An exploratory laparotomy was performed, the findings were: hemoperitoneum of 1500 ml was found, lesion in the bucket loop of 1.2 meters, 1.8 meters from the Treitz angle and 70 cm from the ileocecal valve. We managed with drainage, vascular control, resection of the devascularized intestinal loop and small bowel shotgun stoma were. The patient was transferred to the intensive care unit for hemodynamic management and a second look was performed 5 days after surgery where cavity lavage, stoma dismantling and end-to-end anastomosis of the small intestine in two planes were performed. On post-operative day 7 drains were removed, and the patient was discharged from the surgical service due to improvement, without complications. We recommend a multidisciplinary approach to patients with polytrauma, since they lead to a better and faster recovery, in the same way it allows us to detect and treat any abnormality that impacts the quality of life of patients early.